2018
DOI: 10.1159/000488529
|View full text |Cite
|
Sign up to set email alerts
|

The Role of an Undifferentiated Component in Submucosal Invasion and Submucosal Invasion Depth After Endoscopic Submucosal Dissection for Early Gastric Cancer

Abstract: Background/Aims: The role of an undifferentiated component in submucosal invasion and submucosal invasion depth (SID) for lymph node metastasis (LNM) of early gastric cancer (EGC) with deep submucosal invasion (SID ≥500 μm from the muscularis mucosa) after endoscopic submucosal dissection (ESD) has not been fully understood. This study aimed to clarify the risk factors (RFs), including these factors, for LNM in such patients. Methods: We enrolled 513 patients who underwent radical surgery after ESD for EGC wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…43 In addition, a previous study elucidated that an undifferentiated component in submucosal invasion was an independent predictor for LNM. 44 Although Ishigami et al revealed that there was no evident asscociation between tumor size and the depth of submucosal infiltration (p = 0.1), both submucosal layer invasion and horizontal tumor expansion were significantly correlated with LNM (p < 0.05). 45 For the assessment of the impact of macroscopic appearance on LNM, Sunagawa et al elucidated that the difference for the prevalence of LNM between patients with flat or elevated tumor macroscopic type and patients with depressed tumor macroscopic type was found statistically significant not only in univariate analysis (p = 0.004), but in multivariate analysis as well (p = 0.011), 24 which is consistent with the result of our present pooled analysis (p = 0.002).…”
Section: Number Of Studiesmentioning
confidence: 95%
“…43 In addition, a previous study elucidated that an undifferentiated component in submucosal invasion was an independent predictor for LNM. 44 Although Ishigami et al revealed that there was no evident asscociation between tumor size and the depth of submucosal infiltration (p = 0.1), both submucosal layer invasion and horizontal tumor expansion were significantly correlated with LNM (p < 0.05). 45 For the assessment of the impact of macroscopic appearance on LNM, Sunagawa et al elucidated that the difference for the prevalence of LNM between patients with flat or elevated tumor macroscopic type and patients with depressed tumor macroscopic type was found statistically significant not only in univariate analysis (p = 0.004), but in multivariate analysis as well (p = 0.011), 24 which is consistent with the result of our present pooled analysis (p = 0.002).…”
Section: Number Of Studiesmentioning
confidence: 95%
“…According to the current Japanese gastric cancer treatment guidelines, ESD for EGC-HH is regarded as non-curative if an undifferentiated-type component invades the submucosal layer in SM1 tumor ≤3 cm [1]. Jung et al [12] and Miyahara et al [13] reported that the presence of an undifferentiated component in the submucosal invasion area was a significant risk factor for LN metastasis based on surgical specimens. In the study by Jung et al [12], LN metastasis was found in 36.4% (4/11) of SM1 EGC-HH with a minor poorly differentiated carcinoma component accounting for more than 5% of the tumor area.…”
Section: Discussionmentioning
confidence: 99%
“…This study did not evaluate the LN metastasis rate in EGC-HH with SM1 invasion meeting the expanded curative resection criteria. Miyahara et al [13] reported the LN metastasis rate in EGC-HH cases with deep submucosal invasion (submucosal invasion depth ≥500 µm from the muscularis mucosa). EGC-HH cases with SM1 invasion were not included in the study population.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although undifferentiated type was 0 points in both systems, 51,53 a recent report showed that a submucosal undifferentiated component was an independent risk factor for LNM in patients who underwent additional gastrectomy after ER for submucosal gastric cancer. 56 Therefore, we should be careful in managing patients with a submucosal undifferentiated component even if the patients with undifferentiated-type EGC were regarded as low-risk in the scoring systems.…”
Section: Lymph Node Metastasis In Patients With Additional Gastrectommentioning
confidence: 99%